Impact of coherent mode on divertor particle and heat flux in a type I ELMy H mode plasma on EAST tokamak. (1st September 2022) - Long, F.F.; Zhang, T.; Ming, T.F.; Liu, X.J.; Meng, L.Y.; Wu, M.F.; Li, B.; Liang, R.R.; Wu, M.Q.; Hao, B.L.; Tang, T.F.; Chen, M.W.; et al.
Abstract: The paper investigates the effect of pedestal turbulence, i.e. coherent mode (CM), on the divertor total particle flux, the particle flux distribution and heat flux distribution, and their decay lengths in the scrape-off layer (SOL) region on EAST tokamak. The experimental evidence indicates the coherence between the pedestal CM and the divertor particle flux fluctuation, which implies that the pedestal CM can affect the divertor plasma behavior. The increase of the particle flux decay length ( λ j s ) correlates with the density radial decay length ( λ n, SOL ) in the SOL region where the λ n, SOL is largely affected by the change of pedestal CM amplitude. A quantitative statistical analysis shows that the divertor total particle flux and λ j s in the SOL region increase with increasing amplitude of the electron density fluctuation and the electron temperature fluctuation induced by the pedestal CM. The temporal decay process of the total particle flux is interrupted by the appearance of CM at the pedestal. Meanwhile, the spatial distributions of the divertor particle flux and heat flux are enhanced when the pedestal CM appears, which are observed in both the upper single null and lower single null configurations.